Homologous Recombination Repair Gene Mutations to Predict Olaparib Plus Bevacizumab Efficacy in the First-Line Ovarian Cancer PAOLA-1/ENGOT-ov25 Trial - Pujade-Lauraine E; Brown J; Barnicle A; Wessen J; Lao-Sirieix P; Criscione SW; du Bois A; Lorusso D; Romero I; Petru E; Yoshida H; Vergote I; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Purpose: The PAOLA-1/ENGOT-ov25 trial of maintenance olaparib plus bevacizumab for newly diagnosed advanced high-grade ovarian cancer demonstrated a significant progression-free survival (PFS) benefit over placebo plus bevacizumab, particularly in patients with homologous recombination deficiency (HRD)-positive tumors. We explored whether mutations in non-BRCA1 or BRCA2 homologous recombination repair (non-BRCA HRRm) genes predicted benefit from olaparib plus bevacizumab in PAOLA-1.
Methods: Eight hundred and six patients were randomly assigned (2:1). Tumors were analyzed using the Myriad MyChoice HRD Plus assay to assess non-BRCA HRRm and HRD status; HRD was based on a genomic instability score (GIS) of ≥ 42. In this exploratory analysis, PFS was assessed in patients harboring deleterious mutations using six non-BRCA HRR gene panels, three devised for this analysis and three previously published.
Results: The non-BRCA HRRm prevalence ranged from 30 of 806 (3.7%) to 79 of 806 (9.8%) depending on the gene panel used, whereas 152 of 806 (18.9%) had non-BRCA1 or BRCA2 mutation HRD-positive tumors. The majority of tumors harboring non-BRCA HRRm had a low median GIS; however, a GIS of > 42 was observed for tumors with mutations in five HRR genes (BLM, BRIP1, RAD51C, PALB2, and RAD51D). Rates of gene-specific biallelic loss were variable (0% to 100%) in non-BRCA HRRm tumors relative to BRCA1-mutated (99%) or BRCA2-mutated (86%) tumors. Across all gene panels tested, hazard ratios for PFS (95% CI) ranged from 0.92 (0.51 to 1.73) to 1.83 (0.76 to 5.43).
Conclusion: Acknowledging limitations of small subgroup sizes, non-BRCA HRRm gene panels were not predictive of PFS benefit with maintenance olaparib plus bevacizumab versus placebo plus bevacizumab in PAOLA-1, irrespective of the gene panel tested. Current gene panels exploring HRRm should not be considered a substitute for HRD determined by BRCA mutation status and genomic instability testing in first-line high-grade ovarian cancer.